1982
DOI: 10.1227/00006123-198209000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Brain Water Accumulation after the Central Administration of Vasopressin

Abstract: The intraventricular administration of vasopressin or DDAVP (desmopressin acetate) increased the brain water content from 78.2% to 79.2-79.5%. This was achieved without an accompanying water load. The applied water load alone did not increase the water content of the brain. There was no significant difference in the water content of the brain between animals treated with intraventricular vasopressin and intravenous water load and animals receiving only intraventricular vasopressin. The water content of the olf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

1984
1984
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(25 citation statements)
references
References 0 publications
0
24
0
1
Order By: Relevance
“…There is good evidence, however, that hypoxia and the peptides vasopressin and endothelin, all factors present during ischemia, stimulate activity of the BBB cotransporter. We have found that vasopressin, which is centrally released during ischemia (Dóczi 1993;Landgraf 1992;Ostrowski et al, 1992;Sorensen et al, 1985) and promotes edema formation (Dickinson and Betz, 1992;Dóczi, 1993;Dóczi et al, 1982Dóczi et al, , 1984Hertz et al, 2000;Rosenberg et al, 1990), is also a potent stimulator of the brain microvascular Na-K-Cl cotransporter (O'Donnell et al, 1995a), as is endothelin, which is also released during ischemia (Barone et al, 1994;Kawai et al, 1996bKawai et al, , 1997Spatz et al, 1997). We have shown that vasopressin stimulates the brain endothelial cotransporter by a V1 vasopressin receptor in a manner involving elevation of intracellular [Ca 2+ ] (O'Donnell et al, 1999).…”
Section: Discussionmentioning
confidence: 89%
“…There is good evidence, however, that hypoxia and the peptides vasopressin and endothelin, all factors present during ischemia, stimulate activity of the BBB cotransporter. We have found that vasopressin, which is centrally released during ischemia (Dóczi 1993;Landgraf 1992;Ostrowski et al, 1992;Sorensen et al, 1985) and promotes edema formation (Dickinson and Betz, 1992;Dóczi, 1993;Dóczi et al, 1982Dóczi et al, , 1984Hertz et al, 2000;Rosenberg et al, 1990), is also a potent stimulator of the brain microvascular Na-K-Cl cotransporter (O'Donnell et al, 1995a), as is endothelin, which is also released during ischemia (Barone et al, 1994;Kawai et al, 1996bKawai et al, , 1997Spatz et al, 1997). We have shown that vasopressin stimulates the brain endothelial cotransporter by a V1 vasopressin receptor in a manner involving elevation of intracellular [Ca 2+ ] (O'Donnell et al, 1999).…”
Section: Discussionmentioning
confidence: 89%
“…While the water content of the hemispheres increased by 1.3%, that of the olfactory bulbs did so by 1.7% (32).…”
Section: Distribution and Function Of V2rsmentioning
confidence: 85%
“…In another study (32), intraventricular administration of desmopressin in rats increased the brain water content from 78.2% to 79.2-79.5%. While the water content of the hemispheres increased by 1.3%, that of the olfactory bulbs did so by 1.7% (32).…”
Section: Distribution and Function Of V2rsmentioning
confidence: 90%
“…10 The hormone arginine vasopressin (AVP) was identified as a potential mediator of astrocytic cell swelling and subsequent fulminating edematous changes following cerebral injury. [11][12][13][14][15][16][17] It is thought that centrally-released AVP orchestrates the development of brain edema by inducing water and ionic movement. 18,19 Increased AVP levels activate the V1a receptor (V1aR), facilitate water transport across astrocytic cell membranes, and are associated with brain edema formation.…”
Section: Introductionmentioning
confidence: 99%